2008
DOI: 10.1007/s12144-008-9035-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Identity Style: A Cross-Sectional Analysis

Abstract: The Identity Style Inventory-Revised for a Sixth-Grade Reading Level (ISI-6G) was administered to samples of community college students (N=99) and middle school and high school students (N=320). Tests of between-groups differences indicated that the college sample had a significantly lower mean diffuse-avoidant score on the ISI-6G than the middle and high school sample. In terms of actual assignment to identity styles, college students were significantly more likely to be classified as informational or normati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…With regard to ego identity, Marcia, Waterman, Matteson, Archer, and Orlofsky () proposed that the increasing levels of cognitive development during adolescence are necessary for identity exploration because it involves considering alterative, and often abstract, identities. In addition, empirical work has indicated that as brain function matures individuals tend to demonstrate a more sophisticated identity style (e.g., achieved; Leadbeater & Dionne, ; Phillips, ; Protinsky & Wilkerson, ).…”
Section: A Cultural Ecological Framework Of Biethnic Identitymentioning
confidence: 99%
“…With regard to ego identity, Marcia, Waterman, Matteson, Archer, and Orlofsky () proposed that the increasing levels of cognitive development during adolescence are necessary for identity exploration because it involves considering alterative, and often abstract, identities. In addition, empirical work has indicated that as brain function matures individuals tend to demonstrate a more sophisticated identity style (e.g., achieved; Leadbeater & Dionne, ; Phillips, ; Protinsky & Wilkerson, ).…”
Section: A Cultural Ecological Framework Of Biethnic Identitymentioning
confidence: 99%
“…Development of self-regulatory capacity is associated with identity development [ 82 ]. Although current research is limited, there is good reason to think a relationship between these factors contributes to adolescents identifying as “healthy eaters” or as “exercisers”.…”
Section: Physiological Behavioral and Psychosocial Changes Duringmentioning
confidence: 99%
“…The role of executive function in identity formation has been the focus of theoretical speculation in several studies; however, the empirical evidence is indirect, at best. For example, Phillips (2008) proposed that brain development should play a role in the development of identity, and he interprets increases in identity achievement with age by stating, “Identity scholars can no longer ignore the role played by brain maturation on identity. New knowledge about brain development must be integrated into models of identity if the models are to accurately describe identity processes” (Phillips, 2008, p. 214).…”
Section: Executive Functions and Identity Developmentmentioning
confidence: 99%
“…Executive functions are mediated by the prefrontal cortex of the brain (e.g., Welsh, 2001) and incorporate processes involved in goal-directed behavior (Welsh, Friedman, & Spieker, 2006). Recently, authors have speculated that a relationship exists between executive function and identity (Phillips, 2008; Shanahan & Pychyl, 2007), and research identifying the relationship between identity and career decision-making is well established (Blustein, Devenis, & Kidney 1989; Vondracek, Schulenberg, Skorikov, Gillespie, & Wahlheim, 1995). This literature begs the question whether there are relationships among all three constructs, executive function, identity, and career decision-making, and, if so, what is the nature of this relationship?…”
mentioning
confidence: 99%